Weak-form Efficiency Market Hypothesis: An empirical study on Vietnam stock market - Tran, Nhat (2016)
This study aims to investigate the weak-form efficiency of Vietnam stock market using test of randomness including autocorrelation test, runs test, variance ratio test and unit root tests. The study used daily and weekly data from 16 samples including VN-Index, HNX-Index and ten individual stocks from July 28th, 2000 to June 31st, 2016. The result from all tests consistently indicates that Vietnam stock market is still weak-form inefficient.